Medicine Sales System At Market 3 Mini Medical Pharmacy Web Based - Wilianto Wilianto (Jurnal Minfo Polgan, 2025)
Market 3 Mini Medical Pharmacy is a business that offers medication and medical device sales services. Currently, the pharmacy operates with a conventional system, requiring customers to visit in person for transactions. By implementing a web-based sales system, Mini Medical Pharmacy aims to provide greater convenience, especially for purchasing the necessary medications. The development of this system is carried out using Visual Studio Code as the development tool, with PHP as the programming language and MySQL as the database. The system development follows the Agile Development methodology, with data collection methods including interviews, observation, and literature review.